Islamic Religious Education Learning Model for Deaf Children in Special Schools (SLB) - Rosalinda, Rosalinda; Hakam, Ahmad; Mardhiah, Izzatul (Universitas Pendidikan Indonesia, 2022)
Abstract This study aims to describe and analyze the learning model of Islamic Religious Education (IRE) and its supporting and inhibiting factors for deaf students in a public special school in Jakarta. This research uses a type of qualitative research with descriptive methods. Data collection procedures used are observation, interviews, and documentation. This study concluded that the learning model applied was the Problem-Based Learning Model and the Index Card Math Learning Model. These two learning models make students able to implement the meaning of learning, understand the meaning and content of Al-Qur’an readings, make students understand their obligations as a Muslim and be able to practice them in everyday life. The supporting factors are as follows: strategic school location, supporting facilities and infrastructure, enthusiasm for learning and parental support. While the inhibiting factors are: the lack of linguistic vocabulary, difficulty in communicating with deaf students, and an odd number of students.Abstrak Penelitian ini bertujuan untuk mendeksripsikan dan menganalisis model pembelajaran Pendidikan Agama Islam (PAI) serta faktor pendukung dan penghambatnya pada siswa tunarungu di sebuah SLB Negeri di Jakarta. Penelitian ini menggunakan jenis penelitian kualitatif dengan metode deskriptif. Prosedur pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Penelitian ini menyimpulkan bahwa model pembelajaran yang diterapkan adalah Model Pembelajaran Berbasis Masalah dan Model Pembelajaran Index Card Math. Kedua model pembelajaran ini membuat peserta mampu mengimplementasi makna dari pembalajaran, memahami arti dan isi bacaan Al-Qur’an, membuat siswa paham kewajibannya sebagai seorang muslim serta dapat mengamalkannya pada kehidupan sehari-hari. Adapun faktor pendukung sebegai berikut: lokasi sekolah strategis, sarana dan prasarana yang mendukung, semangat belajar dan dukungan orang tua. Sedangkan faktor penghambatnya, yaitu: minimnya kosakata kebahasaan, kesulitan berkomunikasi dengan siswa tunarungu, dan jumlah siswa yang ganjil.